Associations Between Restrictive Fluid Management and Renal Function and Tissue Perfusion in Adults With Severe Falciparum Malaria: A Prospective Observational Study - Ishioka, H; Plewes, K; Pattnaik, R; Kingston, HWF; Leopold, SJ; Herdman, MT; Mahanta, K; Mohanty, A; Dey, C; Alam, S; Srinamon, K; Mohanty, A; et al. (Oxford University Press, 2019)
Background: Liberal fluid resuscitation has proved harmful in adults with severe malaria, but the level of restriction has not been defined.